The First Total Synthesis of Pectinolides D and E and Total Synthesis of Pectinolides A and C - Sabitha, Gowravaram; AnkiReddy, Praveen; Das, Sukant Kishore (Synthesis, 2015)
The first total synthesis of pectinolides D and E and total synthesis of pectinolides A and C was achieved from a hitherto unknown common key building block prepared from readily available d-mannitol. Key reactions involved in the synthesis are Red-Al reduction of an epoxy alcohol, enantioselective Noyori reduction of ynones, aldehyde–alkyne coupling, and Still–Genari cis-olefination.
Keywords: pectinolides; first synthesis; aldehyde–alkyne coupling; Noyori reduction; Still–Genari cis-olefination